(untitled) (Research, Society and Development, 2020)
The objective of this work was to evaluate the use of Azospirillum brasilense applied in seeds and in the sowing furrow, associated with the use of nitrogen in sowing and cover over the corn crop. The experiment used a randomized block design, with 19 treatments and four repetitions, constituting application modes of A. brasilense (seeds and planting furrow) associated with nitrogen fertilization of sowing and cover. The number of ears per plant, the mass of grains per ear, the mass of one hundred grains, the grain yield, the total nitrogen content and the quantification of diazotrophic bacteria were evaluated. The application of the 300 mL p.c. ha-1 of the inoculant in the planting furrow associated with 20 kg ha-1 of N at sowing and 120 kg ha-1 of N in cover provided the highest grain yield. The productivity of corn grains, the mass of one hundred grains and the N content in the grains are benefited by the use of the bacterium, applied in the seeds or in the cultivation furrow, however, it does not substitute the application of nitrogen, in order to reach high productivity. Seed inoculation in the presence of nitrogen fertilization promoted a greater population of diazotrophic bacteria per gram of root. The amount of Azospirillum sp. per gram of fresh root mass is not correlated with grain yield.